Effects of agrochemical pollution on schistosomiasis transmission: a systematic review and modelling analysis. Issue 7 (July 2020) - Hoover, Christopher M; Rumschlag, Samantha L; Strgar, Luke; Arakala, Arathi; Gambhir, Manoj; de Leo, Giulio A; Sokolow, Susanne H; Rohr, Jason R; Remais, Justin V
Summary: Background: Agrochemical pollution of surface waters is a growing global environmental challenge, especially in areas where agriculture is rapidly expanding and intensifying. Agrochemicals might affect schistosomiasis transmission through direct and indirect effects on Schistosoma parasites, their intermediate snail hosts, snail predators, and snail algal resources. We aimed to review and summarise the effects of these agrochemicals on schistosomiasis transmission dynamics. Methods: We did a systematic review of agrochemical effects on the lifecycle of Schistosoma spp and fitted dose-response models to data regarding the association between components of the lifecycle and agrochemical concentrations. We incorporated these dose-response functions and environmentally relevant concentrations of agrochemicals into a mathematical model to estimate agrochemical effects on schistosomiasis transmission. Dose-response functions were used to estimate individual agrochemical effects on estimates of the agrochemically influenced basic reproduction number, R 0, for Schistosoma haematobium . We incorporated time series of environmentally relevant agrochemical concentrations into the model and simulated mass drug administration control efforts in the presence of agrochemicals. Findings: We derived 120 dose-response functions describing the effects of agrochemicals on schistosome lifecycle components. The median estimate of the basic reproduction number under agrochemical-free conditions, was 1·65 (IQR 1·47–1·79). Agrochemical effects on estimates of R 0 for S haematobium ranged from a median three-times increase ( R 0 5·05, IQR 4·06–5·97) to transmission elimination ( R 0 0). Simulations of transmission dynamics subject to interacting annual mass drug administration and agrochemical pollution yielded a median estimate of 64·82 disability-adjusted life-years (DALYs) lost per 100 000 people per year (IQR 62·52–67·68) attributable to atrazine use. In areas where aquatic arthropod predators of intermediate host snails suppress transmission, the insecticides chlorpyrifos (6·82 DALYs lost per 100 000 people per year, IQR 4·13–8·69) and profenofos (103·06 DALYs lost per 100 000 people per year, IQR 89·63–104·90) might also increase the disability burden through their toxic effects on arthropods. Interpretation: Expected environmental concentrations of agrochemicals alter schistosomiasis transmission through direct and indirect effects on intermediate host and parasite densities. As industrial agricultural practices expand in areas where schistosomiasis is endemic, strategies to prevent increases in transmission due to agrochemical pollution should be developed and pursued. Funding: National Science Foundation, National Institutes of Health.